Risk Management Based IT Analysis Using ISO 31000 (Case Study: PT Bawen Mediatama) - Evinia Evinia; Melkior N. N. Sitokdana (Universitas Bina Darma, 2023)
This study examines the risks of implementing information technology (IT) at PT Bawen Mediatama, a company that has experienced damage to financial institution files due to their IT use. The study uses the ISO 31000 framework to analyze the risks faced by PT Bawen Mediatama, with a focus on identifying the risks and providing recommendations for appropriate risk treatment. The research method is qualitative, and the results indicate that PT Bawen Mediatama faces 20 possible risks, including limited, severe, very severe, and catastrophic level risks. Although the company has implemented risk management, the study concludes that it is not optimal.